The influence of wearing compression stockings on performance indicators and physiological responses following a prolonged trail running exercise - Vercruyssen, F.; Easthope, C.; Bernard, T.; Hausswirth, C.; Bieuzen, F.; Gruet, M.; Brisswalter, J. (European Journal of Sport Science, 2014)
The objective of this study was to investigate the effects of wearing compression socks (CS) on performance indicators and physiological responses during prolonged trail running. Eleven trained runners completed a 15.6 km trail run at a competition intensity whilst wearing or not wearing CS. Counter movement jump, maximal voluntary contraction and the oxygenation profile of vastus lateralis muscle using near-infrared spectroscopy (NIRS) method were measured before and following exercise. Run time, heart rate (HR), blood lactate concentration and ratings of perceived exertion were evaluated during the CS and non-CS sessions. No significant difference in any dependent variables was observed during the run sessions. Run times were 5681.1±503.5 and 5696.7±530.7 s for the non-CS and CS conditions, respectively. The relative intensity during CS and non-CS runs corresponded to a range of 90.5-91.5% HRmax. Although NIRS measurements such as muscle oxygen uptake and muscle blood flow significantly increased following exercise (+57.7% and + 42.6%,+59.2% and + 32.4%, respectively for the CS and non-CS sessions, P<0.05), there was no difference between the run conditions. The findings suggest that competitive runners do not gain any practical or physiological benefits from wearing CS during prolonged off-road running.